Application of computer-assisted navigation in mandibular angle osteotomy - Lin, Liqin (J Int Med Res, 2019)
OBJECTIVE: To compare the effectiveness, accuracy, and surgical safety of a navigation technique with those of a traditional technique for intraoperative mandibular angle osteotomy. METHODS: Forty-three postsurgical patients with mandibular angle hypertrophy who were admitted to our Department from June 2014 to June 2017 were retrospectively reviewed. Of these patients, 23 underwent mandibular angle osteotomy using computer-assisted navigation (navigation group), and 20 underwent osteotomy using a traditional technique (traditional group). Postoperative computed tomography images were analyzed by three-dimensional software. Each patient’s facial proportion indices were measured using Mimics 19.0 software, and statistical comparisons and analyses were performed preoperatively and postoperatively. RESULTS: The postoperative facial contour morphology and facial proportion were improved in both groups; the navigation group showed greater improvement. The difference between the predicted and postoperative values was smaller in the navigation group than traditional group. The postoperative shape of the mandibular angle sample was similar to the preoperative predicted shape in the navigation group. No complications occurred in the navigation group, but paresthesia occurred in 17% of patients in the traditional group. CONCLUSIONS: Mandibular angle osteotomy aided with computer-assisted navigation is more effective, accurate, and safe than the traditional technique and represents a promising clinical approach.